2009
DOI: 10.1111/j.1365-2966.2008.14322.x
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the birth and evolution of the H ii region Sh2-173

Abstract: Based on a multiwavelength study, the interstellar medium around the H ii region Sh2‐173 has been analysed. The ionized region is clearly detected in the optical and the radio continuum images. The analysis of the H i data shows a region of low emissivity that has an excellent morphological correlation with the radio continuum emission. The H ii region is partially bordered by a photodissociation region, which, in turn, is encircled by a molecular structure. The H i and CO structures related to Sh2‐173 are obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 67 publications
3
19
0
2
Order By: Relevance
“…Later on, Cichowolski et al (2009), using the CGPS database (Taylor et al 2003), reported that the H ii region Sh2-173 was born and is evolving onto the borders of a large elliptical feature (whose major and minor axis have angular diameter of 6.…”
Section: Previous H I Work Towards L ∼ 118mentioning
confidence: 99%
“…Later on, Cichowolski et al (2009), using the CGPS database (Taylor et al 2003), reported that the H ii region Sh2-173 was born and is evolving onto the borders of a large elliptical feature (whose major and minor axis have angular diameter of 6.…”
Section: Previous H I Work Towards L ∼ 118mentioning
confidence: 99%
“…of the HII region, that we called G45L, is collecting the molecular gas, as is observed in other HII regions (e.g. Pomarès et al 2009;Cichowolski et al 2009;Deharveng et al 2008). Figure 4 shows the integrated velocity channel maps of the 13 CO J = 1−0 emission every ∼1.25 km s −1 .…”
Section: Fig 2 Two Color Imagesmentioning
confidence: 99%
“…An increasing body of observational evidence confirms the importance of this mechanism (e.g. Patel et al 1998;Oey et al 2005;Arnal & Corti 2007;Cichowolski et al 2009). Given the size of GSH 91.5+2−114, it seems reasonable to expect some signs of recent star-formation activity in or near the shell border.…”
Section: Triggered Star-formation?mentioning
confidence: 95%